Supramolecular aggregates of oligosaccharides with co-solvents in ternary systems for the solubilizing approach of triamcinolone. (20th October 2016) - de Medeiros, Arthur S.A.; Zoppi, Ariana; Barbosa, Euzébio G.; Oliveira, Jonas I.N.; Fernandes-Pedrosa, Matheus F.; Longhi, Marcela R.; da Silva-Júnior, Arnóbio A.
Highlights: Triamcinolone interactions with three oligosaccharides and two co-solvents were investigated. The supramolecular aggregate structure was assessed in a wide experimental approach. Incredibly stable complexes with cyclodextrins were formed with high drug solubilization. Ternary associations stabilized the formation of unimodal complexes. Abstract: A second compound is generally associated with oligosaccharides as a strategy to maximize the solubilizing effect for nonpolar compounds. This study elucidated the role and the mechanism whereby liquid compounds interact in these supramolecular aggregates in the solubilization of triamcinolone. Three different oligosaccharides (beta-cyclodextrin, 2-hydroxipropil-beta-cyclodextrin, and randomly methylated beta-cyclodextrin) and two potent co-solvents (triethanolamine and N- methyl pyrrolidone) were carefully evaluated by using three distinct experimental approaches. Incredibly stable complexes were formed with cyclodextrins (CDs). The structure of the complexes was elucidated by magnetic resonance spectra 2D-ROESY. The interactions of the protons of ring "A" of the drug with H 3 and H 5 protons of the CD cavity observed in the binary complexes remained in both ternary complexes. Unlike the observed ternary associations with triethanolamine, N- methyl pyrrolidone competed with the triamcinolone CD cavity and considerably decreased the stability of the complex and the solubility of the drug. The molecular dynamics (MD) and quantum mechanics:molecular mechanics (QM:MM) calculations supported that triethanolamine stabilized the drug-CD interactions for the conformer identified in the 2D-ROESY experiments, improving the quality and uniformity of the formed complex. The role played by the co-solvent in the ternary complexes depends on its specific ability to interact with the CD cavity in the presence of the drug, which can be predicted in theoretical studies to select the best candidate.